Risk assessment of human consumption of potentially contaminated red swamp crayfish (Procambarus clarkii): a conceptual approach - Lages, Nuno (2009)
Pretende-se aprofundar o conceito da análise de risco inerente ao consumo humano de crustáceos contaminados com xenobióticos. Deu-se particular importância à análise do consumo do lagostim vermelho da louisiana (procambarus clarkii), espécie invasora não indígena que nos últimos anos assumiu um inusitado destaque no âmbito ambiental e gastronómico português. compilaram-se dados disponíveis na literatura sobre a possível contaminação deste organismo, no sentido de permitir uma avaliação ecotoxicológica e estabelecer uma ligação entre a contaminação deste recurso e efeitos potenciais toxicológicos em humanos. Our goal was to deepen the concept of risk assessment associated to human consumption of crustacean species contaminated by anthropogenic xenobiotics. consumption of red swamp crawfish (procambarus clarkii), an invasive species that has recently assumed a leading role in portugal, both environmentally and gastronomically, is emphasized. Data was compiled from published literature, concerning its possible contamination, in order to allow an ecotoxicological assessment and to establish a link between contamination of this resource and toxicological potential effects on humans.